Disaster Laws and Policies, Suppressing Intergenerational Transmission of Women in Small-Scale Fishing in Patani - Hasamoh, Alisa (King Prajadhipok’s Institute Journal, 2023)
This research article aims to study poverty’s intergenerational transmission (IGT) on women in small-scale fishermen in disaster situations in Moo. 1 Tamboon Bangtawa, Ampour Nong Chik, Pattani Province. There was a group of 10 informants. This qualitative research used the historical method of genealogy, narrative (storytelling), life history lines and family plants of poor households across generations. The research tools are the study of policies and national economic social development plans on poverty, semi-structured and in-depth questionnaires, observations, and analysis using data consideration principles to create the main points and analyse them together. This research paper has the main argument that although the disaster is an "event" that causes the villagers to experience difficulties in their lives. It becomes a condition that leads to poverty across generations of women in this village. In this research, "Structural disaster" is not just an event. It relates to the structure and power of relations between the state and its citizens. It can pass laws and actions to Malay Muslim citizens in the area, particularly villagers in small fishing groups in the village. These are causing a catastrophic event, and it becomes a permanent disaster. Moreover, there are mangrove and fishery laws that limit and oppress communities. The structure of relations between capital and villagers was in a battle for fishery resources. The researcher conceptualized the research framework from literature reviews on cross-generational poverty and disasters. The fisherman’s community has a way of life-related to the sea and the coast. Also, villagers have experienced coastal erosion disasters for the past 70 years until they had to retreat deep into the mangrove forest coast. Later, when the new house was declared a reserved forest area. As a result, the fishermen lacked social opportunities because they could not pledge or mortgage their homes and land or expand their business in other ways. Since childhood, all case studies have been hard work. When women enter the early stages of old age, they encounter health problems such as spinal nerve compression. Children have little education like their father and mother generation. They are causing the generation of children to lack opportunities to work and develop professional skills. However, the child has to take care of the mother, who is sick and starts to enter the elderly age because the primary health care system is inaccessible. Therefore, it has become a recurring cycle of poverty across generations that is difficult to escape.